1976
DOI: 10.1002/1097-0142(197611)38:5<1925::aid-cncr2820380510>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Improved outlook for Ewing's sarcoma with combination chemotherapy (vincristine, actinomycin D and cyclophosphamide) and radiation therapy

Abstract: Vincristine, actinomycin D, and cyclophosphamide (VAC) were administered to 14 patients with Ewing's sarcoma. The primary tumors were treated with radiation therapy and concurrent chemotherapy. Nine patients had no visible metastases at diagnosis: two died following the development of pulmonary metastases and the rest have been free of disease for periods varying from 4 months to 4 1/2 years following completion of treatment. This contrasts with a 27% survival in patients previously treated at this center with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
5

Year Published

1980
1980
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(48 citation statements)
references
References 23 publications
0
43
0
5
Order By: Relevance
“…This tumor is chemosensitive, and multimodal therapy has significantly improved outcome for patients with EFT (3-year survival rates 55-80%). [6][7][8][9][10] Despite these encouraging results, subgroups of patients who have a poor prognosis can be identified (survival of 10-30% at 3 years). Poor prognostic features at initial presentation include metastatic disease, particularly those with bone or BM involvement, bulky disease (48 cm diameter) at diagnosis, primary tumor involving axial (pelvic) or proximal (femur and humerus), shorter interval of EFS between diagnosis and relapse 6 and age older than 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor is chemosensitive, and multimodal therapy has significantly improved outcome for patients with EFT (3-year survival rates 55-80%). [6][7][8][9][10] Despite these encouraging results, subgroups of patients who have a poor prognosis can be identified (survival of 10-30% at 3 years). Poor prognostic features at initial presentation include metastatic disease, particularly those with bone or BM involvement, bulky disease (48 cm diameter) at diagnosis, primary tumor involving axial (pelvic) or proximal (femur and humerus), shorter interval of EFS between diagnosis and relapse 6 and age older than 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year survival rate of the patients without metastases at diagnosis was 47.5%, not different from that reported by several investigators, 6,17 but lower than that described by others. 5,7,12 The factors contributing to low long-term survival rate in our patients included advanced stage of tumor at diagnosis and shorter duration of chemotherapy (median 8 months) because of lack of compliance, instead of 18 months of therapy administered by other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Megavoltage irradiation has significantly improved the long-term survival in patients with localized Ewing's sarcoma. 4,7 The efficacy of chemotherapy in the management of Ewing's sarcoma was noted 20 years ago when several studies showed that chemotherapy can induce remission in patients with advanced disease. 8,.11 Since a fair number of patients with localized Ewing's sarcoma develop systemic metastases despite local therapy, such as surgical resection or radiotherapy, chemotherapy was used in conjunction with radiotherapy with the hope of improving the long-term survival of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heretofore, simply referred to as Ewing sarcoma, this sarcoma subtype is a highly aggressive malignancy of adolescents and young adults (7) that is rapidly fatal without effective multimodality treatment that includes surgery and/or radiation and extensive use of systemic chemotherapy. Although polychemotherapy has led to marked improvement in 5-year survival for patients diagnosed with localized Ewing sarcoma-approaching 80% with current generation clinical trials-those with metastatic disease or rapid tumor recurrence fare poorly and often quickly succumb to their disease (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%